(untitled) (Development Service Industry Management, 2025)
The article provides an analytical review of modern technologies for analyzing cryptocurrencies. It is established that for effective forecasting of cryptocurrency markets it is necessary to use a wide range of tools that provide an integrated approach to analysis. It is found that today such well-known analytical platforms as CoinMarketCap, Glassnode, CoinGlass, as well as other systems for cryptocurrency analysis offer significant functionality. The article highlights the main functionalities and features of these platforms, describes their interface, and also indicates their advantages and disadvantages. A comparative characterization of the considered platforms is carried out according to the following criteria: data analysis; integration with other systems; availability of online metrics and social signals; forecasting efficiency and security. The comparison allowed us to determine that the most optimal choice for traders is platforms that integrate with other systems for in-depth analysis of market sentiment, such as Glassnode, CoinMarketCap. For tasks requiring high accuracy of forecasts, you should pay attention to CoinGlass. The article focuses on the use of artificial intelligence to analyze market sentiment, model price trends, and integrate analytical platforms for traders. It is established that artificial intelligence allows reducing investment risks and provides more accurate forecasting of price movements. As a result, the author identifies the main trends in the development of cryptocurrency analytics technologies, among which the most important are the expansion of the functionality of platforms for integration and forecasting, as well as the introduction of new artificial intelligence tools to improve the accuracy of analysis.